2005
DOI: 10.1103/physreve.71.046404
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond electrical explosion of thin aluminum wires in a vacuum: Experimental and computational investigations

Abstract: Experimental and computational investigations of nanosecond electrical explosion of a thin Al wire in vacuum are presented. We have demonstrated that increasing the current rate leads to increased energy deposited before voltage collapse. The experimental evidence for synchronization of the wire expansion and light emission with voltage collapse is presented. Hydrocarbons are indicated in optical spectra and their influence on breakdown physics is discussed. The radial velocity of low-density plasma reaches a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…that accompany these wire explosions, and their important applications (bright source of radiation, fast opening switches, etc.). [1][2][3][4][5] Different electrical, optical, spectroscopic, and x-ray diagnostic methods have been developed and used to study and characterize the time-dependent evolution of the exploding matter. Optical diagnostics are effective to measure the radius of the boundary of the exploding wire.…”
Section: Introductionmentioning
confidence: 99%
“…that accompany these wire explosions, and their important applications (bright source of radiation, fast opening switches, etc.). [1][2][3][4][5] Different electrical, optical, spectroscopic, and x-ray diagnostic methods have been developed and used to study and characterize the time-dependent evolution of the exploding matter. Optical diagnostics are effective to measure the radius of the boundary of the exploding wire.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one should take special measures to suppress surface breakdown. A significant increase in energy deposition into a metal core prior to the plasma corona formation was demonstrated in experiments by Sarkisov et al [9][10][11] using special dielectric coating.…”
Section: Introductionmentioning
confidence: 92%
“…[8][9][10][11][12][13][14] However, maintaining controlled parameters under these conditions has proved to be a constant challenge amongst researchers. Further, using EWs, it has been observed that non-negligible avalanche-type increases in electrical conductivity are associated with the application of an electric field.…”
mentioning
confidence: 99%